Quasi-experiment in the educational reality - Sirotová, Mariana; Michvocíková, Veronika; Rubacha, Krzysztof (Journal of Education Culture and Society, 2021)
Aim. The main aim of the study is a presentation of the results of a quasi-experiment related to using a serious game in the preparation phase of supervised teaching practice as well as during its completion. Methods. The main method of the study is a quasi-experiment with the factor rotation technique. The method comprised two phases with two unequal groups of surveyed university students. In the first phase, the experimental influence was investigated in the first group and the second group served as the control group (to compare the results). In the second phase, the groups were switched around in the quasi-experiment; the control group became the experimental group and vice versa. Results. The presented study has a theoretical-empirical character. In the theoretical part, the characteristics of quasi-experiment and its use are briefly discussed. In the empirical part, the quasi-experiment is applied to the educational reality of future teachers. Supervised practice teaching is an important part of the university education of future teachers. Using a serious game therein is a positive element also when it comes to the development of students’ approach towards supervised teaching practice. Conclusion. Quasi-experiment is used as an experimental method for verification of examined reality. In the educational reality, its realisation is more difficult because it is a more demanding environment than a laboratory one. By realising the quasi-experiment, the theoretical supposition about the positive influence of serious games on the development of a university student’s personality can be confirmed.